Novel polymer based photoresist and preparation thereof
By adjusting the content ratio of acetoxystyrene and hydroxystyrene copolymer, the existing photoresist compositions are solved by complex preparation and poor photolithography performance, and a significant line width roughness is achieved Reduce and improve lithography performance.
Patent Information
- Application Number
- CN202310693382.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-13
AI Technical Summary
The preparation of existing chemical amplification photoresist compositions is complex and difficult to control, resulting in poor photolithography performance, especially the difficulty of reducing linewidth roughness (LWR).
Two simple and easy-to-prepared copolymer mixtures: acetoxystyrene copolymer and hydroxystyrene copolymer, optimize the lithographic performance by adjusting their content ratio, including copolymer (A) with dissolution inhibition and photoacid The dissociated group, the copolymer (B) has a combination of alkali-soluble and photoacid dissociable groups, forming a photoresist composition.
The linewidth roughness (LWR) is significantly reduced, and better lithographic performance is achieved, with the specific effect being greater than 50%, preferably greater than 60%, and preferably greater than 70%.
Smart Images

Figure CN119126487A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to novel polymers and compositions containing the polymers, thereby providing polymer-based photoresists for different applications in KrF and extreme ultraviolet lithography (EUVL). The photoresist composition of the present invention comprises a mixture of an acetoxystyrene copolymer containing a photoacid dissociable group and a hydroxystyrene copolymer containing a photoacid dissociable group. Background Art
[0002] Chemically amplified photoresist compositions typically contain copolymers having an alkali-soluble moiety, a dissolution-inhibiting moiety, and a photoacid-dissociable moiety. These copolymers, made from three or more different monomers, are structurally complex, and their reproducible preparation is extremely challenging. As a result, control of the batch-to-batch preparation of the polymer is very difficult, making control of the polymer composition almost impossible.
[0003] There is still a need in the art to obtain a new chemically amplified photoresist composition comprising a copolymer that is simple in structure and easy to prepare, and at the same time, the new chemically amplified photoresist composition can achieve improved lithographic performance. Summary of the invention
[0004] The present invention relates to a mixture of two simple and easily prepared copolymers. The chemical structures of the two copolymers are very similar, and therefore their mixture is homogeneous without phase separation.
[0005] Additionally, by adjusting the content of each copolymer in the mixture, desired properties required for enhanced lithographic performance can be obtained. The inventors of the present invention have unexpectedly discovered that the photoresist compositions of the present invention can exhibit significantly improved lithographic performance, including reduced line width roughness.
[0006] The present invention relates to a novel chemically amplified photoresist composition, comprising a mixture of two copolymers of a copolymer (A) and a copolymer (B), wherein:
[0007] The copolymer (A) is an acetoxystyrene copolymer having a dissolution inhibiting acetoxy group and a photoacid dissociable group; and
[0008] The copolymer (B) is a hydroxystyrene copolymer having an alkali-soluble hydroxyl group and a photoacid-dissociable group.
[0009] Preferably, the content of copolymer (A) is at least 1% by weight, based on the total weight of the mixture of the two copolymers of copolymer (A) and copolymer (B).
[0010] Preferably, the content of copolymer (A) is 5 to 15 wt %, for example 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 13 wt %, 14 wt %, 15 wt %, etc., based on the total weight of the mixture of the two copolymers of copolymer (A) and copolymer (B).
[0011] Preferably, based on the total weight of the mixture of the two copolymers of copolymer (A) and copolymer (B), the content of copolymer (B) is 85 wt % to 95 wt %, for example 85 wt %, 86 wt %, 87 wt %, 88 wt %, 89 wt %, 90 wt %, 91 wt %, 92 wt %, 93 wt %, 94 wt %, 95 wt %, etc.
[0012] The photoacid-dissociable groups contained in the copolymer (A) and the copolymer (B) are selected from the following: alkyl ester groups, alicyclic ester groups, or combinations thereof.
[0013] Preferably, the photoacid-dissociable group is a (meth)acrylate group, which means a methacrylate group or an acrylate group.
[0014] Preferably, the photoacid-dissociable group is selected from the following: an alkyl (meth)acrylate group, an alicyclic (meth)acrylate group, or a combination thereof.
[0015] Preferably, the photoacid cleavable group is an alkyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl.
[0016] Preferably, the photoacid-dissociable group is a tert-butyl (meth)acrylate group.
[0017] Preferably, the photoacid-dissociable group is an alicyclic (meth)acrylate group selected from a 1-alkyl-1-cycloalkyl (meth)acrylate group and a 2-alkyl-2-adamantyl (meth)acrylate group.
[0018] Preferably, the photoacid cleavable group is a 1-alkyl-1-cycloalkyl (meth)acrylate group, wherein the alkyl group is selected from the following: methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl; and the cycloalkyl group is selected from the following: cyclopentyl, cyclohexyl and cycloheptyl.
[0019] Preferably, the photoacid cleavable group is a 2-alkyl-2-adamantyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl.
[0020] Preferably, the photoacid-dissociable group is a combination of a 1-alkyl-1-cycloalkyl(meth)acrylate group and / or a 2-alkyl-2-adamantyl(meth)acrylate group and / or a tert-butyl(meth)acrylate group.
[0021] Optionally, copolymer (A) and / or copolymer (B) may also contain additional styrene groups.
[0022] Copolymer (A)
[0023] The copolymer (A) is a random copolymer, and it may be a binary copolymer, a ternary copolymer or a tetraary copolymer.
[0024] The copolymer (A) is prepared by copolymerization of acetoxystyrene monomer and one or more comonomers.
[0025] The comonomer is selected from the following: (meth)acrylate monomer and styrene monomer. (Meth)acrylate monomer refers to methacrylate monomer or acrylate monomer.
[0026] The copolymer (A) can be prepared by copolymerizing an acetoxystyrene monomer and a (meth)acrylate monomer.
[0027] Alternatively, the copolymer (A) may be prepared by copolymerization of acetoxystyrene monomers, (meth)acrylate monomers and styrene monomers.
[0028] Based on the total moles of the monomers of the copolymer (A), the content of the acetoxystyrene monomer ranges from 50 mol % to 99 mol %, for example, 50 mol %, 55 mol %, 60 mol %, 65 mol %, 70 mol %, 75 mol %, 80 mol %, 85 mol %, 90 mol %, 95 mol % and 99 mol %, etc.
[0029] The (meth)acrylate monomer is contained in an amount ranging from 5 mol % to 30 mol %, for example, 5 mol %, 10 mol %, 15 mol %, 20 mol %, 25 mol %, 30 mol %, etc., based on the total moles of the monomers of the copolymer (A).
[0030] If present, the styrene monomer is present in an amount ranging from 1 mol% to 20 mol%, for example, 1 mol%, 5 mol%, 10 mol%, 15 mol%, 20 mol%, etc., based on the total moles of monomers of copolymer (A).
[0031] Styrene monomer may also be absent.
[0032] (Meth)acrylate monomers are selected from the following:
[0033] Alkyl (meth)acrylate monomers, alicyclic (meth)acrylate monomers, or a combination thereof.
[0034] Regarding the (meth)acrylic acid alkyl ester monomer, the alkyl group is selected from the following:
[0035] Methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl.
[0036] Preferably, the alkyl (meth)acrylate monomer is tert-butyl (meth)acrylate monomer.
[0037] The alicyclic (meth)acrylate monomer is selected from 1-alkyl-1-cycloalkyl (meth)acrylate monomers and 2-alkyl-2-adamantyl (meth)acrylate monomers.
[0038] With respect to the 1-alkyl-1-cycloalkyl (meth)acrylate group, the alkyl group is selected from the following:
[0039] methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, and isopentyl; and cycloalkyl is selected from the group consisting of cyclopentyl, cyclohexyl, and cycloheptyl.
[0040] With respect to the 2-alkyl-2-adamantyl (meth)acrylate monomer, the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, and isopentyl.
[0041] Alternatively, the (meth)acrylate monomer is a combination of a 1-alkyl-1-cycloalkyl (meth)acrylate monomer and / or a 2-alkyl-2-adamantyl (meth)acrylate monomer and / or a tert-butyl (meth)acrylate monomer.
[0042] The preparation method of copolymer (A) is well known in the art. Typically, copolymer (A) is prepared by free radical polymerization of acetoxystyrene monomer and one or more comonomers in the presence of a free radical initiator. Preferably, the free radical initiator is AIBN (azobisisobutyronitrile).
[0043] The weight average molecular weight (Mw) of the copolymer (A) is 5,000-25,000 Daltons. Preferably, the weight average molecular weight (Mw) of the copolymer (A) is 8,000-15,000 Daltons.
[0044] The weight average molecular weight (Mw) of the copolymer (A) is measured by GPC (gel permeation chromatography).
[0045] GPC (gel permeation chromatography) is used for weight average molecular weight (Mw) determination. The GPC system uses an HPLC constant flow pump (isocratic pump), an automatic sample injector, an RI (refractive index) detector and a micro-polystyrogel column. Monodisperse standards of polystyrene are used to generate a calibration graph for evaluating the Mw of unknown samples.
[0046] The polydispersity of copolymer (A) is 1.2-4.0. Preferably, the polydispersity of copolymer (A) is 1.2 to 2.5.
[0047] Copolymer (B)
[0048] The copolymer (B) is a random copolymer, and it may be a binary copolymer, a ternary copolymer, or a tetraary copolymer.
[0049] The preparation method of copolymer (B) is well known in the art. Generally, copolymer (B) is prepared by saponifying a copolymer of acetoxystyrene monomer and one or more (meth)acrylate monomers and optionally styrene monomer using a base in a non-aqueous solvent, wherein the (meth)acrylate monomer is as described above.
[0050] Preferably, the monomer type and monomer content of copolymer (B) are the same as those of copolymer (A), except that the acetoxystyrene monomer is replaced by a hydroxystyrene monomer.
[0051] Preferably, the base may be ammonium hydroxide. Preferably, the non-aqueous solvent may be methanol.
[0052] The weight average molecular weight (Mw) of the copolymer (B) is 5,000-25,000 Daltons. Preferably, the weight average molecular weight (Mw) of the copolymer (B) is 8,000-15,000 Daltons.
[0053] The weight average molecular weight (Mw) of the copolymer (B) is measured by GPC (gel permeation chromatography).
[0054] GPC (Gel Permeation Chromatography) is used for weight average molecular weight (Mw) determination. The GPC system uses an HPLC constant flow pump, an autosampler, an RI (refractive index) detector, and a micro polystyrene gel column. Monodisperse standards of polystyrene are used to generate a calibration graph for evaluating the Mw of unknown samples.
[0055] The polydispersity of copolymer (B) is 1.2-4.0. Preferably, the polydispersity of copolymer (B) is 1.2 to 2.5.
[0056] The present invention relates to a novel chemically amplified photoresist composition, comprising:
[0057] (a) a mixture of two copolymers of copolymer (A) and copolymer (B), wherein copolymer (A) and copolymer (B) are as defined above;
[0058] (b) a solvent or a mixture of solvents;
[0059] (c) a photoacid generator; and
[0060] (d) a base as a quencher; and
[0061] (e) Optionally, a surfactant.
[0062] Based on the total weight of the chemically amplified photoresist composition, the content of component (a) (i.e., the mixture of two copolymers of copolymer (A) and copolymer (B)) is preferably in the range of 5 wt % to 25 wt %, for example, 5 wt %, 10 wt %, 15 wt %, 20 wt %, 25 wt %, etc.
[0063] Based on the total weight of the chemically amplified photoresist composition, the content of component (b) (i.e., the solvent or the mixture of solvents) is preferably in the range of 60 wt % to 85 wt %, for example, 60 wt %, 65 wt %, 70 wt %, 75 wt %, 80 wt % and 85 wt %, etc.
[0064] Based on the total weight of the chemically amplified photoresist composition, the content of component (c) (i.e., the photoacid generator) is preferably in the range of 0.5 wt % to 15 wt %, for example, 0.5 wt %, 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 13 wt %, 14 wt % and 15 wt %, etc.
[0065] Based on the total weight of the chemically amplified photoresist composition, the content of component (d) (i.e., the base as a quencher) is preferably in the range of 0.1 wt % to 5 wt %, for example, 0.1 wt %, 0.5 wt %, 1 wt %, 1.5 wt %, 2 wt %, 2.5 wt %, 3 wt %, 3.5 wt %, 4 wt %, 4.5 wt % and 5 wt %, etc.
[0066] If present, component (e) (i.e., surfactant) is preferably present in an amount ranging from 0.1 wt % to 2.0 wt %, such as 0.1 wt %, 0.5 wt %, 1.0 wt %, 1.5 wt %, 2.0 wt %, etc., based on the total weight of the chemically amplified photoresist composition.
[0067] The solvent of the chemically amplified photoresist composition may be selected from the following: cyclohexanone, cyclopentanone, γ-butyrolactone, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, ethyl lactate, 2-methylcyclohexanone, 2-heptanone, propylene carbonate and mixtures thereof.
[0068] The photoacid generator of the chemically amplified photoresist composition may be an ionic photoacid generator, for example, comprising iodine. and sulfonium compounds Salt compounds.
[0069] The photoacid generator of the chemically amplified photoresist composition can be a non-ionic photoacid generator, such as imidosulfonate compounds, N-sulfonyloxyimide compounds; diazosulfonyl compounds and other sulfone photoacid generators, including α,α-methylene disulfone, disulfone hydrazine and disulfonylamine salts; nitrobenzyl compounds, halogenated, especially fluorinated non-ionic photoacid generators.
[0070] The base of the chemically amplified photoresist composition may be an organic base, such as an amine or an ammonium salt.
[0071] The surfactant may be selected from silicone polymers having pendant polyether groups such as XIAMETER TM OFX-3667, XIAMETER TM OFX-0190、DOWSIL TM OFX-0400, XIAMETER TM OFX-5098、VORASURF TM DC 5103, XIAMETER TM OFX-5220、DOWSIL TM OFX-5247、DOWSIL TM OFX-5329, XIAMETER TM OFX-5330、SYLGARD TM OFX-0309, XIAMETER TM OFX-5211、VORASURF TM TF 5067, Silsurf A004, SilsurfA008, Silsurf A010, Silsurf C208, Silsurf D208, Silsurf D212, Silwet L 7604, SilwetL 7608, Silwet L 7609, Silwet L 408, Silwet L 618, Silwet L 625.
[0072] Variation of the content of copolymer (A) and copolymer (B) in the mixture will provide precise control of the polymer composition and address the challenging reduction of line width roughness (LWR).
[0073] The photoresist composition of the present invention can achieve a % reduction in line width roughness (LWR) of greater than 50%, preferably greater than 60%, and preferably greater than 70%. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 A comparison of line width roughness (LWR) values of AxBx (photoresist composition of the invention) and Bx (control photoresist) using a scanning electron microscope (SEM) of a "line-and-space pattern" with a line width of 450 nm is shown. Example
[0076] The following examples illustrate the technical solutions of the present invention and are not intended to limit the scope of the present invention.
[0077] Example 1: Synthesis of Copolymer A1
[0078] Poly(4-acetoxystyrene-co-tert-butyl methacrylate) (80 / 20, molar ratio): 81.0 g (0.5 mol) of 4-acetoxystyrene, 17.75 g (0.125 mol) of tert-butyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried under vacuum at 50° C. to produce a white powder (Mw=12,800 and Mw / Mn=2.1).
[0079] Example 2: Synthesis of Copolymer A2
[0080] Poly(4-acetoxystyrene-co-tert-butyl methacrylate) (75 / 25, molar ratio): 81.0 g (0.5 mol) of 4-acetoxystyrene, 23.71 g (0.167 mol) of tert-butyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with water 1.0 L and dried under vacuum at 50° C. to produce a white powder (Mw=12,000 and Mw / Mn=2.13).
[0081] Example 3: Synthesis of Copolymer A3
[0082] Poly(4-acetoxystyrene-co-tert-butyl methacrylate) (70 / 30, molar ratio): 81.0 g (0.5 mol) of 4-acetoxystyrene, 30.47 g (0.215 mol) of tert-butyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with 1.0 L of water and dried under vacuum at 50° C. to produce a white powder (Mw=13,850 and Mw / Mn=1.59).
[0083] Example 4: Synthesis of Copolymer A4
[0084] Poly(4-acetoxystyrene-co-styrene-co-tert-butyl methacrylate) (60 / 20 / 20, molar ratio): 60.75 g (0.375 mol) of 4-acetoxystyrene, 13.0 g (0.125 mol) of styrene, 17.75 g (0.125 mol) of tert-butyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with water 1.0 L and dried under vacuum at 50° C. to produce a white powder (Mw=14,810 and Mw / Mn=1.8).
[0085] Example 5: Synthesis of Copolymer A5
[0086] Poly(4-acetoxystyrene-co-styrene-co-tert-butyl methacrylate) (60 / 15 / 25, molar ratio): 60.75 g (0.375 mol) of 4-acetoxystyrene, 9.75 g (0.094 mol) of styrene, 22.15 g (0.156 mol) of tert-butyl methacrylate and 6.0 g of AIBN were dissolved in 400 mL of THF. The resulting solution was degassed and added dropwise to 100 mL of THF at 60° C. under nitrogen atmosphere over 3.0 h. The solution was further stirred at 60° C. under nitrogen for another 24 h and then cooled to room temperature. The mixture was diluted with 250 ml of THF and added dropwise to 2.5 liters of DI water and stirred. The precipitated polymer was filtered, rinsed with water 1.0 L and dried under vacuum at 50° C. to produce a white powder (Mw=13,310 and Mw / Mn=1.34).
[0087] Example 6: Synthesis of copolymer B1
[0088] 10 grams of copolymer A1 from Example 1, 20 grams of ammonium hydroxide (28-30%) and 100 mL of methanol were heated at 65° C. with stirring for 18 h. The resulting solution was precipitated in 500 mL of HCl solution (5%). After stirring for 30 min, the resulting powder was filtered. Rinse with 150 mL of water and dry under vacuum at 50° C. to provide a white powder (Mw=12,200 and Mw / Mn=1.85).
[0089] Example 7: Synthesis of Copolymer B2
[0090] 10 grams of copolymer A2 from Example 2, 20 grams of ammonium hydroxide (28-30%) and 100 mL of methanol were heated at 65° C. with stirring for 18 h. The resulting solution was precipitated in 500 mL of HCl solution (5%). After stirring for 30 min, the resulting powder was filtered. Rinse with 150 mL of water and dry under vacuum at 50° C. to provide a white powder (Mw=11,500 and Mw / Mn=1.92).
[0091] Example 8: Synthesis of Copolymer B3
[0092] 10 grams of copolymer A3 from Example 3, 20 grams of ammonium hydroxide (28-30%) and 100 mL of methanol were heated at 65° C. with stirring for 18 h. The resulting solution was precipitated in 500 mL of HCl solution (5%). After stirring for 30 min, the resulting powder was filtered. Rinse with 150 mL of water and dry under vacuum at 50° C. to provide a white powder (Mw=12,590 and Mw / Mn=1.52).
[0093] Example 9: Synthesis of Copolymer B4
[0094] 10 grams of copolymer A4 from Example 4, 20 grams of ammonium hydroxide (28-30%) and 100 mL of methanol were heated at 65° C. with stirring for 18 h. The resulting solution was precipitated in 500 mL of HCl solution (5%). After stirring for 30 min, the resulting powder was filtered. Rinse with 150 mL of water and dry under vacuum at 50° C. to provide a white powder (Mw=12,930 and Mw / Mn=1.69).
[0095] Photoresist preparation (control photoresist and photoresist of the present invention)
[0096] Four photoresist compositions were prepared and are referred to herein as photoresists A1B1, A2B2, and A3B3, respectively.
[0097] Photoresist A1B1 contains 10 wt % of copolymer A1 and 90 wt % of copolymer B1, based on the total weight of copolymer A1 and copolymer B1.
[0098] Photoresist A2B2 contains 5 wt % of copolymer A2 and 95 wt % of copolymer B2, based on the total weight of copolymer A2 and copolymer B2.
[0099] Photoresist A3B3 contains 10 wt % of copolymer A3 and 90 wt % of copolymer B3, based on the total weight of copolymer A3 and copolymer B3.
[0100] In addition, each of the photoresists A1B1, A2B2, A3B3 was prepared as follows: a mixture of copolymer Ax and copolymer Bx was dissolved in an appropriate solvent (propylene glycol monomethyl ether acetate), and a quencher (tetramethylammonium hydroxide pentahydrate, 0.6 wt% of the total copolymer), PAG (triphenylsulfonium trifluorosulfonate, 5.0 wt% of the total copolymer) and a surfactant (Silwet L7604, at 0.5 wt% of the total solids) were added to the resulting solution. The formulation of the control resist was the same, except that only copolymer B was used instead of the mixture of copolymer A and copolymer B. The control photoresists are referred to herein as photoresists B1, B2, B3 and B4.
[0101] All photoresists were prepared at 20 wt% solids in an appropriate solvent (propylene glycol monomethyl ether acetate) and then filtered through a 0.2 μm filter.
[0102]
[0103] Lithography performance
[0104] The photoresist solution was spin coated on a silicon wafer treated with an organic anti-reflective coating of 60 nm thickness. Coating was performed under standard solution spin coating to provide a film with a thickness of 1400 nm after soft baking at 130° C. for 60 seconds. The resulting film was exposed to a 0.53 numerical aperture KrF excimer laser stepper followed by post-exposure baking at 110° C. for 60 seconds. The resulting film was developed using 0.263N tetramethylammonium hydroxide solution in double developer surface dwell mode (double puddle mode) for 40 seconds (20 / 20 second process).
[0105] A SEM CG6300 (HITACHI CD-SEM) instrument with the following parameters was used:
[0106] Accelerating voltage 800V Probe current 5.0pA Magnification 149997 Digital zoom 1 Frame rate 16 Image Rotation 0.0 degrees Optics high resolution Pixel 512,512 Automatic EF close Detector ratio 30% Detector Node SE+EF
[0107] The photoresist layer was patterned with a “line and space pattern” of 450 nm line width, and the patterned resist layers were analyzed on scanning electron microscope (SEM) images to evaluate their LWR (line width roughness) ( Figure 1 ).
[0108] Figure 1 It is clearly shown that the photoresist composition of the present invention has a lower LWR than that of the comparative example.
[0109] Table 1 LWR of photoresist compositions A1, B1 and B1
[0110]
[0111] Table 2 LWR of photoresist compositions A2, B2 and B2
[0112]
[0113] Table 3 LWR of photoresist compositions A3, B3 and B3
[0114]
[0115] As can be seen from Tables 1-3 above, the photoresist compositions of the present invention achieve a % reduction in LWR of greater than 50%, preferably greater than 60%, and preferably greater than 70%, compared to the control photoresist composition.
[0116] While the invention has been described with respect to specific embodiments, the details thereof should not be construed as limiting, as it will be apparent that various embodiments, changes and modifications may be made without departing from the spirit and scope thereof, and it should be understood that such equivalent embodiments are intended to be included within the scope of the invention.
Claims
1. A composition comprising a mixture of two copolymers of copolymer (A) and copolymer (B), wherein: The copolymer (A) is an acetoxystyrene copolymer having a dissolution inhibiting acetoxy group and a photoacid dissociable group; and The copolymer (B) is a hydroxystyrene copolymer having an alkali-soluble hydroxyl group and a photoacid-dissociable group.
2. The composition according to claim 1, wherein the content of copolymer (A) is 5 to 15 wt %, and the content of copolymer (B) is 85 to 95 wt %, based on the total weight of the mixture of the two copolymers of copolymer (A) and copolymer (B).
3. The composition according to any one of claims 1 to 2, wherein the photoacid dissociable groups contained in copolymer (A) and copolymer (B) are selected from the following: alkyl ester groups, alicyclic ester groups or combinations thereof; Preferably, the photoacid dissociable group is selected from the following: an alkyl (meth)acrylate group, an alicyclic (meth)acrylate group, or a combination thereof; Preferably, the photoacid-dissociable group is an alkyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl; Preferably, the photoacid dissociable group is an alicyclic (meth)acrylate group selected from a 1-alkyl-1-cycloalkyl (meth)acrylate group and a 2-alkyl-2-adamantyl (meth)acrylate group; Preferably, the photoacid cleavable group is a 1-alkyl-1-cycloalkyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl; and the cycloalkyl group is selected from the group consisting of cyclopentyl, cyclohexyl and cycloheptyl; and Preferably, the photoacid cleavable group is a 2-alkyl-2-adamantyl (meth)acrylate group, wherein the alkyl group is selected from the group consisting of methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl and isopentyl.
4. The composition according to any one of claims 1 to 3, wherein the photoacid-dissociable group is a tert-butyl(meth)acrylate group and / or a 1-alkyl-1-cycloalkyl(meth)acrylate group and / or a 2-alkyl-2-adamantyl(meth)acrylate group.
5. The composition according to any one of claims 1 to 4, wherein copolymer (A) and copolymer (B) contain additional styrene groups.
6. The composition according to any one of claims 1 to 5, wherein the weight average molecular weight (Mw) of copolymer (A) is 5,000-25,000 Daltons; preferably, the weight average molecular weight (Mw) of copolymer (A) is 8,000-15,000 Daltons; and the polydispersity of copolymer (A) is 1.2-4.0, preferably, the polydispersity of copolymer (A) is 1.2 to 2.5; and wherein the weight average molecular weight (Mw) of copolymer (B) is 5,000-25,000 Daltons; preferably, the weight average molecular weight (Mw) of copolymer (B) is 8,000-15,000 Daltons; and the polydispersity of copolymer (B) is 1.2-4.0, preferably, the polydispersity of copolymer (B) is 1.2 to 2.
5.
7. A chemically amplified photoresist composition comprising: (a) a mixture of two copolymers of the copolymer (A) and the copolymer (B) according to any one of claims 1 to 6; (b) a solvent or a mixture of solvents; (c) a photoacid generator; and (d) a base as a quencher; and (e) Optionally, a surfactant.
8. The chemically amplified photoresist composition according to claim 7, wherein the content of component (a) ranges from 5 wt% to 25 wt%, the content of component (b) ranges from 60 wt% to 85 wt%, the content of component (c) ranges from 0.5 wt% to 15 wt%, the content of component (d) ranges from 0.1 wt% to 5 wt%, and if present, the content of component (e) ranges from 0.1 wt% to 2.0 wt%, based on the total weight of the chemically amplified photoresist composition.
9. A method for producing the chemically amplified photoresist composition of any one of claims 7 to 8, comprising mixing each of components (a), (b), (c), (d) and optionally (e).
10. Use of the chemically amplified photoresist composition according to any one of claims 7 to 8 to reduce line width roughness.
